FORCED LABOR OF DEPORTED PEOPLES IN THE INDUSTRY OF SOUTHERN KAZAKHSTAN (the example of Kentau city) - Shetkus, Benediktas; Pazilov, Ye. (Journal of history, 2018)
One of the most tragic pages in the history of the Greeks was Stalin’s deportation. Almost the majority of the Greeks, who lived on the north-eastern coast of the Black Sea, were deported to Kazakhstan. The article is considered the deportation of the Pontic Greeks in the South Kazakhstan region and their role in the development of industry and agriculture in the region. The purpose of this article is an attempt to restore the chronological order of the deportation of Greeks, their resettlement and employment in the city Kentau, within the framework of the concept of the history of everyday life. This article consists of two separate parts.The first part is considered deportations of Pontic Greeks to South Kazakhstan. The second section talks about the formation of Greek communities in the city Kentau. And also it is said about the use of labor of the deported Greeks in industry.